Strengthening the BMT Ecosystem through Sharia Cooperative Workshop, Indonesia - Oyong Lisa; Ratnaningsih Ratnaningsih; Titis Srimurni; Prasojo Ashar Nur Darmawan (Trescode Green Organization, 2026)
The purpose of this activity is to strengthen the BMT ecosystem through increasing the capacity of sharia cooperative management to be more professional and sustainable. The methods used include the planning, implementation, and evaluation stages, involving actors, actors, and the community as informants so that the perspective produced is more comprehensive. The results of the activity showed an increase in participants' understanding of the governance of sharia cooperatives and the formation of inter-institutional networks that expanded access to capital and strengthened BMT's position in the sharia financial ecosystem. An important finding from this activity is that a participatory approach through workshops is able to produce practical solutions that are relevant to the needs of micro enterprises while increasing public trust in BMT. The qualitative analysis used succeeded in capturing socio-economic and cultural dynamics so that the resulting recommendations were more contextual and sustainability-oriented. This activity also supports the results of previous research that emphasizes the importance of sharia-based governance and institutional innovation. Thus, the sharia cooperative workshop can be seen as a strategic instrument in building an inclusive, competitive, and community-oriented BMT ecosystem. This abstract emphasizes that the activities carried out in April 2026 at the Burza Hotel Jogjakarta make a real contribution to strengthening the BMT ecosystem through collaboration with integrity and innovation.